EVALUASI KEBIJAKAN USAHA MIKRO KECIL DAN MENENGAH DI KABUPATEN BANDUNG - Robbani, Bintang Putri Latifatul; Wulandari, Rafih Sri (Ilmu Pemerintahan Universitas Langlangbuana, 2023)
This research is motivated by the not optimal evaluation of policies on micro and small and medium enterprises in Bandung Regency. Based on the background of the researcher identifies the problem as follows: How to evaluate micro small and medium business policies in Bandung Regency. The theory used in this study is the policy evaluation theory of William Dunn in Subarsono (2011: 126) which includes four dimensions, namely effectiveness, efficient, adequacy, equity, responsiveness, accuracy. Based on the theory approach, researchers formulate propositions of evaluation of micro small and medium business policies in Bandung Regency will run optimally when carrying out indicators which include effectiveness, efficient, adequacy, equity, responsiveness, accuracy. The method used qualitative methods with descriptive. The data collection techniques are obtained through: observation, interviews, and documentation. The results of the observations and interviews produce data which are then analyzed by researchers as a basis for further explanation and explanation in this study. The results of research from the evaluation of micro small and medium business policies in Bandung Regency have not been running optimally because they have not been optimally in the dimensions of effectiveness, efficient, adequacy, equity, responsiveness, accuracy. This is because there are still many elements of the apparatus who still cannot meet the 6 indicators. There are still many things that have not been realized so that the planned policy program has not yet reached all micro and small and medium enterprises in Bandung Regency.